Effect of Shear Rate on Characteristics, Performance and Morphology of Polysulfone Blend Membranes - Asmadi, Ali; R. M., Yunus; Mohamad, Awang; Anwar, Johari; Ramli, Mat (scientific.net, 2015)
Rheological factor such as shear rate during membrane fabrication process has an effect on properties, structures and performance of membranes. Flat sheet asymmetric PSf/CAP blend membranes were prepared using an automatic casting machine at different shear rates in the range of 42.0 to 201.0 s-1. Results showed that increasing the shear rate from 42.0 to105 s-1 has increased the molecular orientation and thickness which then reduces the water content, porosity and pure water flux of PSf/CAP blend membranes. However, further increasing the shear rate beyond 105 s-1has resulted in an increase in the water content of PSf/CAP blend membranes.